CADRE SATISFACTION IN USING THE SI CETING APPLICATION AS AN INFORMATION AND EDUCATION MEDIA FOR STUNTING PREVENTION IN LEMINGGIR VILLAGE, MOJOSARI DISTRICT, MOJOKERTO REGENCY - Elies Meilinawati S. Budihartini (International Journal of Nursing and Midwifery Science (IJNMS), 2026)
Cadres play an important role in delivering health education to prevent stunting. The use of digital educational media is expected to improve access to accurate information and support cadres in carrying out health promotion activities. This study aimed to determine cadres' satisfaction with the use of the SI CETING application as an information and education media for stunting prevention. This study employed a descriptive quantitative design. The research was conducted among cadres in a rural area. A total of 31 respondents were selected using total sampling. Data were collected using a user satisfaction questionnaire after participants had used the SI CETING application. The data were analyzed using descriptive statistics and presented as frequencies and percentages. All respondents reported positive satisfaction with the application. Eighteen respondents (58.1%) were categorized as satisfied, while thirteen respondents (41.9%) were categorized as very satisfied. No respondents reported dissatisfaction. These findings indicate that the application was well accepted and perceived as a useful digital medium for delivering health information and education related to stunting prevention. The SI CETING application demonstrated a high level of user satisfaction among cadres, indicating its potential as a digital educational tool to strengthen community-based health promotion and support stunting prevention programs.